1995
DOI: 10.1159/000119316
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diazepam and Buspirone on Reaction Time of Saccadic Eye Movements

Abstract: Effects of the anxiolytic drugs diazepam and buspirone were studied on the reaction time of saccadic eye movements. The study was performed with 8 healthy volunteers in a double-blind, placebo-controlled way. The purpose was to investigate the putative drug effects on the first step of an attention shifting task: the disengagement of attention. Saccadic reaction time was measured in two conditions: the ‘gap’ and the ‘overlap’ condition. In the first condition a delay is present between the offset of a fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The literature search yielded 56 different studies using 16 different benzodiazepines, published since 1966 [14–67]. There were 173 different tests used, on average 3.1 tests per study.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 56 different studies using 16 different benzodiazepines, published since 1966 [14–67]. There were 173 different tests used, on average 3.1 tests per study.…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown that drugs can affect eye movements [75]. Fafrowicz et al [76] have highlighted an increase in saccadic RT in healthy volunteers treated by anxiolytic drugs. Green et al [77] have also demonstrated an increase in antisaccade errors in schizophrenic patients treated by benzodiazepine.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind placebo-controlled design, the effects of the benzodiazepine diazepam and the 5-HT 1A partial agonist buspirone were investigated using a prosaccade task with a fixation point gap overlap manipulation (see glossary) (Fafrowicz et al, 1995). Both drugs are used to treat anxiety disorders, but buspirone which also has mixed agonist/antagonist effects on postsynaptic dopamine receptors and no apparent GABA-ergic effects, is much less sedating.…”
Section: Pharmacologic Effects On Eye Movements In Healthy Individmentioning
confidence: 99%
“… 5-HT, serotonin; ACh, acetylcholine; anti, antisaccade; DA, dopamine; GABA, aminobutyric acid; GLU, glutamate; NE, norepinephrine; pro, prosaccade; SPEM, smooth pursuit eye movement. 1 Avila et al (2003). 2 Avila et al (2002). 3 Ball et al (1991). 4 Barrett et al (2004). 5 Bittencourt et al (1980). 6 Bittencourt et al (1981). 7 Bittencourt et al (1983). 8 Cohen et al (1985). 9 Condy et al (2005). 10 de Visser et al (2001). 11 Depatie et al (2002). 12 Domino et al (1997). 13 Fafrowicz et al (1995). 14 Flechtner et al (1992). 15 Friedman et al (1994). 16 Gijsman et al (1998). 17 Gijsman et al (2002). 18 Glue (2007). 19 Godaux et al (1990). 20 Green et al (1998). 21 Green et al (2000). 22 Green et al (1996). 23 Hamilton et al (1993). 24 Hoffmann et al (1993) 25 Holzman et al (1975). 26 Hommer et al (1986). 27 Jansen et al (1988). 28 King (1994). 29 King et al (1995). 30 Larrison-Faucher et al (2004). 31 Lynch et al (1997). 32 Malaspina et al (1994). 33 Mandema et al (1992). 34…”
Section: Text Boxmentioning
confidence: 99%